2018
DOI: 10.31943/afiasi.v3i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Berhubungan dengan Kejadian Carpal Tunnel Syndrome (CTS) pada Karyawan SPBE Di Indramayu

Abstract: CTS merupakan gangguan umum yang berhubungan dengan pekerjaan, disebabkan oleh gerakan berulang dan posisi yang menetap pada jangka waktu lama. Beberapa faktor diketahui menjadi risiko terjadinya CTS, seperti gerakan berulang dengan kekuatan, tekanan pada otot, postur kerja yang tidak ergonomik dan lain-lain. Penelitian ini menggunakan Cross Sectional dengan jumlah sampel 40 karyawan di dua SPBE bagian Filling Hall area. Fisher Exact Test digunakan untuk analisis data uji statistik. Variabel yang ditelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The longer a person works in a company, the more the feeling of saturation of his work will affect the level of fatigue he experiences (Nurhalizah, Syam and Sulaeman, 2023). Carpal Tunnel Syndrome (CTS) complaints are most commonly found in workers with long working periods; this is because the increase in working period will make workers make repetitive movements continuously, which in this case can be the main factor that causes workers to experience complaints of Carpal Tunnel Syndrome (CTS) (Muthoharoh, Basri K and Nuraeni, 2018). Where the results of statistical tests using Fisher Exact Test values, obtained probability) so that it can be concluded that there is a relationship between length of service and the incidence of Carpal Tunnel Syndrome (CTS) in SPBE employees in Indramayu in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The longer a person works in a company, the more the feeling of saturation of his work will affect the level of fatigue he experiences (Nurhalizah, Syam and Sulaeman, 2023). Carpal Tunnel Syndrome (CTS) complaints are most commonly found in workers with long working periods; this is because the increase in working period will make workers make repetitive movements continuously, which in this case can be the main factor that causes workers to experience complaints of Carpal Tunnel Syndrome (CTS) (Muthoharoh, Basri K and Nuraeni, 2018). Where the results of statistical tests using Fisher Exact Test values, obtained probability) so that it can be concluded that there is a relationship between length of service and the incidence of Carpal Tunnel Syndrome (CTS) in SPBE employees in Indramayu in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Saat dilakukannya pemeriksaan akan terasa nyeri yang terlokalisir pada pergelangan tangan dan dapat menjalar ke jari-jari. 7 Dengan demikian dari penelitian yang dilakukan kepada mahsiswa ini didapatkan hasil adanya hubungan posisi wrist saat menggenggam smartphone terhadap tingkat nyeri pada mahasiswa dengan risiko carpal tunnel syndrome.…”
Section: Hubungan Posisi Wrist Saat Menggenggam Smartphone Terhadap T...unclassified
“…Tidak ergonomisnya postur kerja serta dilakukan dalam kondisi statis akan menimbulkan CTS dimana salah satu penyebab timbulnya CTS karena adanya peradangan pada jaringan otot, saraf dan menimbulkan pembengkakan dan menekan saraf medianus yang ada di pergelangan tangan. 22 Penelitian fitriani (2012) menyebutkan bahwa posisi pergelangan tangan yang ekstrim atau tidak ergonomis dapat menimbulkan CTS dimana risikonya 4 kali lebih besar dapat terjadi. Maka dari itu usahakan posisi pergelangan tangan saat menggunakan keyboard tidak menumpu di meja atau tangan tidak melakukan gerakan menekuk terus menerus.…”
Section: Hubungan Postur Pergelangan Tangan Dengan Kejadian Carpal Tu...unclassified